Effect of Hepatic Macrophage Polarization and Apoptosis on Liver Ischemia and Reperfusion Injury During Liver Transplantation - Ye, Liping; He, Saiqin; Mao, Xinli; Zhang, Yu; Cai, Yue; Li, Shaowei (Frontiers in Immunology, 2020)
Ischemia-reperfusion injury (IRI) is a kind of injury caused by limited blood supply and subsequent blood supply recovery during liver transplantation. Serious ischemia-reperfusion injury is the main cause of transplant failure. Hepatic IR is characterized by tissue hypoxia due to limited blood supply and reperfusion inducing oxidative stress and immune response. Studies have confirmed that Kupffer cells (KC), resident macrophages in the liver, play a key role in aseptic inflammation induced by IRI. In the liver macrophage polarization, M1 macrophages activated by interferon-γ (IFN-γ) and lipopolysaccharide (LPS) have a pro-inflammatory effect and release a variety of inflammatory cytokines. M2 macrophages activated by IL-4 have an anti-inflammatory response. M1type of KCs is the dominant players in the IRI as it can secret various pro-inflammatory cytokines to exacerbate the injury and recruit other types of immune cells from the circulation. On the other hand, M2 type of KCs can also serve as a contrary way to ameliorate IRI by unregulated the anti-inflammatory factors. Moreover, new standpoint has been putting forward that KCs apoptosis may have function in different way to influence the IRI. Managements towards KCs are expected to be the effective way to improve the IRI. This review summarizes the effects of hepatic macrophages polarization and apoptosis in liver IRI.